Criminal Jurisprudence in India (International Journal of Food and Nutritional Sciences, 2022)
In the scenario of India, the goal of this study is to look at plea bargaining and see why it hasn't been a huge success. The document is separated into three parts: the first segment analyzes the procedure of plea bargaining in India, a relatively new idea in criminal jurisprudence; the second section discusses the rationale why so Code of Criminal Procedure had already remained a dead letter, differentiating it with the procedure of criminal prosecutions in the United States, where it is widely used; and the third section mentions the explanations why the Code of Criminal Procedure has managed to stay a dead letter, contrasting that with the process of plea bargaining in the United The purpose of this article is to suggest that the failure of the plan may be linked to the failure of the whole justice delivery system. In India, there have been many instances of criminals putting it in meals or contacting the irritating poisonous components of the plants with the victim's body in buses/trains. Poisonous plants are biological weapons that may cause severe health issues or even death. Professional poisoners in toxi-crime like these weapons because they are readily accessible and inexpensive. They've played such a big role in romance and crime that even students of human nature are interested in learning more about them. The writers of this article researched several hazardous and poisonous plants found in India that are often utilized by criminals to commit crimes. All of the toxicological chemicals found in these plants are included in this article, providing a comprehensive database for forensic toxicologists.